Phenacyl bromide as Norrish type I photoinitiator for the facile synthesis of chain-end functional PMMA and polystyrene - Kati, Mina; Cakir, Yusra Bahar; Kaya, Kerem; Kiliclar, Huseyin Cem; Kiskan, Baris (Frontiers in Materials, 2024)
Phenacyl bromide has been explored as a new Norrish Type I photoinitiator for radically polymerizing methyl methacrylate and styrene monomers. A straightforward radical photopolymerization method using UVA light for the synthesis of chain-end functional poly(methyl methacrylate) and polystyrene has been developed. The process has been refined for both bulk and solution photopolymerizations. Chain-end functionalization was demonstrated by the formation of block-copolymers of the bromineended homopolymers, utilized as macroinitiators, resulting in an increase in the molecular weight of the corresponding precursor, observed by gel-permeation chromatography (GPC). Block copolymerization was initiated by radicals generated at the chain-ends by a halogen-atom transfer reagent, namely, dimanganese decacarbonyl (Mn2(CO)10). This simple light-induced method is promising for the additive manufacturing field such as vat photopolymerization, stereolithography, digital light processing as it yields chain-end functional materials that can be further processed.